Longitudinal assessment of fluorescence stability shows fluorescence intensity decreases over time: implications for fluorescence microscopy studies - Sean C. Sweat; Sarah P. R. Berg; Tenzin Kunkhyen; Emma G. Foster; Claire E. J. Cheetham (PLoS ONE, 2026)
Immunohistochemistry (IHC) is one of the most widely used techniques across basic, translational, and clinical sciences. Key considerations need to be made to achieve reliable and robust IHC staining, however what has been understudied is the stability of IHC signal intensity over time. Changes in signal intensity over time have significant implications for data analysis and interpretation and ultimately impact scientific conclusions. In order to explore changes in IHC signal, the stability of fluorescence intensity was assessed over the course of six weeks using widefield or confocal microscopy. Results indicate that fluorescence intensity can decrease over this time course and that whether this decrease occurs and to what extent is influenced by the selection of the primary antibody as well as that of the secondary antibody, primary-secondary antibody combination, and utilization of chemical staining versus IHC staining. This investigation reinforces best practices for imaging fluorescent staining to ensure accurate and reliable data collection, be it for cell counting, assessing protein expression levels, or marker colocalization.